Influential factors of online fraud occurrence in retailing banking sectors from a global prospective: An empirical study of individual customers in the UK and China. (9th March 2015) - Sun, Yan; Davidson, Ian
Abstract : Purpose: – This paper aims to focus on online fraud occurrence in retailing banking sectors both in the UK and China. Online financial transactions bring convenience to individuals dramatically and improve banking service quality efficiently. However, the latest service channel, Internet, has been exploited by fraudsters excessively, standing at a huge monetary loss worldwide. Design/methodology/approach: – In aspects of demographic factors, financial activities and IT usage, results would benefit financial organisations and local authorities in strengthening customers' education and improving policymaking. The fraud occurrence model is empirically tested using quantitative data, and comparison is discussed using qualitative data collected in both countries. Findings: – The findings provide solid understanding of customers' behaviours towards online financial transactions and fraud occurrence internationally. As the main implication, customer education is proposed to benefit financial organisations in both countries. According to the data collection process and the data analysis results, individual customers are aware of banking policies and practices to some extent. Particularly in China, customers' satisfaction level is relatively lower and service quality is not reasonable in most circumstances. Research limitations/implications: – The research experiences gained from this study suggest a number of areas for future research, particularly the under-researched area of fraud. Rather than approaching the research questions through individuals, there would be much value in working with merchants and financial organisations that are dealing with financial transactions and fraud on a daily basis. Originality/value: – By combining three approaches (demographic factors, financial activities and IT usage), this study is trying to develop a comprehensive and statistical understanding of online fraud occurrences.